Chapter 22: Beet Production in Florida - George J. Hochmuth; Donald N. Maynard; Charles S. Vavrina; William M. Stall; Kenneth L. Pernezny (EDIS)
This document is HS721, Horticultural Sciences Department, UF/IFAS Extension. Published December 2005.